Regional Integration & Trade in SubSaharan Africa: An Analysis - Nyamache, Tom (Kabarak university, 2013)
Regional integration in the SSA is no shortcut; its instead a requirement. Member states, however poor, backward and isolated require political goodwill and support. Trade blocs enhance the co-operation in the region though it hasn’t worked.
Keywords: Regional Integration